Hubungan Stres dengan Frekuensi Serangan pada Pasien Asma di RSUD Dr. Moewardi - Ramadhian, Elsa Adila; Subagio, Yusup; ., Sutanto; Murti, Bhisma (Nexus Kedokteran Klinik, 2012)
Background: Asthma is a respiratory inflamation disease with symptoms such as cough, wheeze, uplifted chest, shortness of breath. Previews studies assumsed that asthma has psychosomatic component that is predominated by psychoanalysis. Stress and psychologic factors had been assosiated with asthma symptoms, bronco-constriction and reduction in average pulmonary flow in patients with asthma. This study aimed to determine the assosiation between stress and asthma frequency in patients with asthma. Methods: This analytic study was observational using cross-sectional approach. A sample of 50 study subjects was selected by exhaustive sampling from outpatients who visited Pulmonary Clinics, RSUD Dr. Moewardi Surakarta. The data was collected by interview using a set of questionnaire. The data was annalyzed using multiple logistic regression model on SPSS 20 for windows. Results: Asthmatic patients with high level of stress had 13,39 times as many risk of having asthma attacks then those with low level of stress. This estimate had controlled for the effects of confounding variables such as exposure to cigarette smoke, use of controller, age, and gender. Conclusion: There is a statisticaly significant assosiation between stress and frequency of asthma attack in patient with asthma. This conclusion is drawn after controlling for the effects of confounding variables such as exposure to cigarrete smoke, use of controller, age, and gender. Keywords: stress, asthma Â